Insect protein-based composite film incorporated with E. purpurea-based nanoparticles augmented the storage stability of parmesan cheese - Shubam Singh; Hina F. Bhat; Sunil Kumar; Rana Muhammad Aadil; Gholamreza Abdi; Zuhaib F. Bhat (Heliyon, 2024)
The objective of this study was to prepare an insect protein-based composite film containing plant extract-based nanoparticles to augment the lipid and microbial stability of cheese. An ultrasonication-mediated green method of synthesis was followed to develop the nanoparticles using E. purpurea flower extract (EP-NPs). The film was developed using locust protein (Loc-Pro) and different levels of EP-NPs [2.0% (T3), 1.5% (T2), 1.0% (T1), and 0.0% (T0)]. It was characterised and evaluated for efficacy using parmesan cheese (Par-Che) as a model system stored for 90 days (4 ± 1 °C). The addition of EP-NPs markedly enhanced the antioxidant and antimicrobial activities of the Loc-Pro-based film as indicated by the results of radical-scavenging activity (ABTS and DPPH), total-flavonoid and total-phenolic contents, ion-reducing potential (FRAP), and inhibitory halos (mm). It also increased (P < 0.05) the density (g/ml), redness (a*), and yellowness (b*) and reduced (P < 0.05) the WVTR (mg/m2t), transparency (%) and lightness (L*) of the Loc-Pro-based film. The film incorporated with EP-NPs showed a marked desirable impact on protein oxidation, lipid stability, microbial quality and antioxidant potential of Par-Che during 90 days of storage. While cheese samples without any film showed mean values of 2.24 mg malondialdehyde/kg, 0.79% oleic acid, 1.22 nm/mg protein, 2.52 log CFU/g and 1.24 log CFU/g on day 90 for TBARS, FFA, total carbonyl content, total plate count and psychrophilic count, samples within T3 films showed significantly lower values of 1.82, 0.67, 0.81, 2.15, and 0.81, respectively. A positive impact of the Loc-Pro-based film was found on the sensory characteristics of Par-Che. Both the Loc-Pro-based film and the digestion simulation improved the radical-scavenging activity and ion-reducing potential of the Par-Che. Our results indicate the potential of Loc-Pro-based film as a means to enhance the storage quality of cheese.